Changes in Income Poverty Risks at the Transition from Unemployment to Employment: Comparing the Short-Term and Medium-Term Effects of Fixed-Term and Permanent Jobs - Michael Gebel; Stefanie Gundert (Social Indicators Research, 2023)
Unemployment is a major risk factor of poverty and employment is regarded key to overcoming it. The present study examines how the income poverty risk of unemployed individuals changes in the short and medium term, when they take up work, and whether the effects differ according to the type of employment. The focus is on permanent and fixed-term job contracts, as the political promotion of fixed-term employment has often been framed as an effort to reduce long-term unemployment and poverty. Drawing on longitudinal data from the German panel study 'Labour Market and Social Security' (PASS) 2010–18, we apply a first difference estimator with asymmetric effects to examine the effect of starting a job out of unemployment on income poverty risks in the subsequent four years. Strikingly, starting in a fixed-term and permanent contract have similarly strong and lasting poverty-reducing effects in the short and medium term. Thus, with regard to risks of income poverty, starting a permanent job does not appear more beneficial than starting a fixed-term job for unemployed persons. We discuss the reasons for this finding and also explore how the poverty-reducing effects of transitions from unemployment to fixed-term versus permanent employment vary by household type, occupation, working time and firm size.
Keywords: 300; Income poverty; Unemployment; Fixed-term employment; Labour market transitions; First difference estimator